2013
DOI: 10.7764/laje.50.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Governance and foreign direct investment in Latin America: A panel gravity model approach

Abstract: It is widely argued that good governance is an important determinant of foreign direct investment (FDI). With the exception of studies of corruption, however, empirical research on the link between governance and FDI is limited, particularly in the context of Latin America. Moreover, recent studies by Bellos and Subasat (2012a and 2012b) suggest that poor governance is a source of attraction rather than a hurdle for multinational companies in selected transition countries. By employing a panel data gravity mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 36 publications
0
40
0
2
Order By: Relevance
“…More recently, the basic form of the gravity model approach has been largely developed and successfully applied to analyze the effects of institutional and policy factors on FDI inflows (e.g. Bannaga, Gangi, Abdrazak, & Al‐Fakhry, ; Bellos & Subasat, ,b; Bénassy‐Quéré, Coupet, & Mayer, ; Subasat and Bellos, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the basic form of the gravity model approach has been largely developed and successfully applied to analyze the effects of institutional and policy factors on FDI inflows (e.g. Bannaga, Gangi, Abdrazak, & Al‐Fakhry, ; Bellos & Subasat, ,b; Bénassy‐Quéré, Coupet, & Mayer, ; Subasat and Bellos, ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the literature generally supports the widespread idea that good institutional infrastructure and governance play a critical role in attracting FDI, some empirical studies have found conflicting results that indicate adverse effects of governance indicators on FDI inflows (see, e.g. Blonigen & Piger, 2011;Chakrabarti, 2001;Cheung and Qian, 2009;Gangi and Abdrazak, 2012;Kolstad and Wiig, 2012;Li & Resnick, 2003;Méon & Sekkat, 2004;and Okeahalam and Bah, 1998;Subasat and Bellos, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One line of argument stresses that higher FDI inflows are strongly linked with good institutions (Globerman et al, 2004). In another way, Cuervo-Cazurra (2008) argues that the high costs of doing business associated with uncertainty are majorly caused by weak governance, while the more contrasting view posits that poor and bad governance system will attract more multinational companies(MNCs) to select developing economies which in turn promote growth in the respective recipient economies (Subasat and Bellos, 2013). On the other hand, the role of good institutions in the economic development process has been confirmed to be positively and significantly profound in modern economies (North, 1990;Verspagen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have specifically focused on the connection of rule of law with FDI inflow, though there is no unanimity on the nature of the nexus. For instance, Staats and Biglaiser (2012), Gammoudi and Cherif (2015), Büthe and Milner (2014), Jandhyala, (2013), Al-Khouri (2015), Jadhav (2012), Anyanwu (2012), Azam et al (2012), Karim et al (2012), Rodríguez-Pose and Cols (2017), Jeong (2014), Osabutey and Okoro (2015), Ahmad and Ahmed (2014), Gangi and Abdulrazak (2012), Hoa and Lin (2016), Lee et al (2014), Nnadi and Soobaroyen (2015), Fung and Garcia-Herrero (2012), De Beule and Duanmu (2012), Ferreira and Ferreira (2016), Różański and Sekuła (2016) and Osabuohien and Efobi (2013) have documented from their studies in various contexts that the relationship of rule of law with FDI is positively significant, insisting that improvement in the level of adherence to the rule of law stimulates FDI inflow.On the contrary,Bellos and Subasat (2012) andSubasat and Bellos (2013) reported from their analysis of selected transition economies and countries of Latin American, respectively that rule of law has an inverse relationship with FDI, arguing that lack of observance of rule of law is not an impediment, but a means of encouraging FDI inflow. On their part,Khan and Akbar (2013), Al-Khouri and Khalik (2013), Gobinda and Haider (2014), Bannaga et al (2013), Kurul and Yalta (2017) and Saidi et al (2013) concluded from their various empirical investigations that ROL has insignificant influence on the inflow of FDI.…”
mentioning
confidence: 96%